DOI: 10.11606/d.11.2008.tde-15072008-124634
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da flutuação sérica de anticorpos maternos nos períodos pré e pós-parto e transferência de imunidade passiva em cabritos recém-nascidos utilizando colostro bovino e caprino

Abstract: Estudo da flutuação sérica de anticorpos maternos nos períodos pré e pós-parto e transferência de imunidade passiva em cabritos recémnascidos utilizando colostro bovino e caprino Anali Linhares Lima Piracicaba 2008 Dissertação apresentada para obtenção do Título de Mestre em Agronomia. Área de concentração: Ciência Animal e Pastagens

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
6

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
2
2
0
6
Order By: Relevance
“…On the other hand, variations that could characterize a peak of concentration were not observed in OC. In accordance with the present study, Lima (2008) observed the highest serum IgG concentration in newborn goat kids fed bovine colostrum at 48.75 ± 0.72 h of life. The author did not observe maximum value in the animals fed caprine colostrum.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, variations that could characterize a peak of concentration were not observed in OC. In accordance with the present study, Lima (2008) observed the highest serum IgG concentration in newborn goat kids fed bovine colostrum at 48.75 ± 0.72 h of life. The author did not observe maximum value in the animals fed caprine colostrum.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the highest serum IgG concentrations were observed in BC animals, with the maximum value at 24 h. Pauletti et al (2003), Machado Neto et al (2004 and Lima (2008) observed similar pattern in calves and goat kids that received colostrum with high antibody concentration. On the other hand, variations that could characterize a peak of concentration were not observed in OC.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Nos bovinos, a concentração de IgG representa 35 a 47% da fração protéica, apresentando alta relação entre as duas variáveis (MACHADO NETO et al, 2004;PAULETTI et al, 2007). Nos ovinos e caprinos, em média 35% da proteína total sérica corresponde a imunoglobulinas (HALLIDAY, 1974;LIMA, 2008). A correlação da flutuação de IgG e proteína total neste período de vida do animal pode chegar a 0,81 em ovinos e 0,78 nos bovinos (HALLIDAY, 1974;PACKER, 1986;PAULETTI et al, 2002;KINDLEIN et al, 2007).…”
Section: Imunoglobulinas E Proteína Total Séricaunclassified